FRI0479 Serum Free Light Chains of Immunoglobulins Are Associated with Disease Activity in Systemic Sclerosis: A Prospective and Controlled Study. (10th June 2014) - Lanteri, A.; Dubucquoi, S.; Hachulla, E.; Langlois, C.; Lambert, M.; Vuye, S.; Hauspie, C.; Hatron, P.-Y.; Launay, D.
Abstract : Background: There is a free light chains excess production over immunoglobulin heavy-chain synthesis by B lymphocytes. Serum free light chains (SFLC) are high in monoclonal gammapathy and can serve as a diagnosis tool for myeloma. Recent studies have suggested that SFLC are higher in autoimmune diseases like Sjögren syndrome, lupus or rheumatoid arthritis than in healthy population, and could be interesting biomarkers for disease activity assessment. There are no data in systemic sclerosis (SSc). Objectives: To determinate if SFLC are higher in SSc vs healthy population, and if the level of SFLC correlates with disease activity or severity. Methods: 134 patients with SSc were prospectively enrolled. Following data were gathered: age at diagnosis, SSc subtypes, visceral involvement, biological manifestations including the other B cell activation markers (rheumatoid factor, beta2-microglobuline, BAFF, levels of gammaglobulins), SSc activity and severity scores. SFLC were assessed by Combylite® (The Binding Site, Birmingham, UK) in patients and in a control group of 401 blood donors matched for age and sex. Results: Mean and median SFLC values were significantly higher in SSc than in controls (median: 19.99 mg/L, mean 24.03 mg/L vs median 15.43 mg/L, mean 17.50 mg/L, respectively, p<0.05). In univariate analysis, there was a significant correlation between SFLC and the modified Rodnan score, past digital ulcers, systolic pulmonary arterial pressure, DLCO and EUSTAR as well as Medsger scores. SFLC were also correlated with erythrocyte sedimentation rate, CRP, and with all the B cell activation markers (IgG, IgA, and IgM levels, rheumatoid factor, beta2-microglobuline, and BAFF). The multivariate analysis found a significant positive correlation between SFLC and the presence of an interstitial lung involvement and its severity (Medgser pulmonary score), past digital ulcers, the IgG and IgA levels, rheumatoid factor, beta2-microglobuline, and BAFF. Conclusions: Our study is the first to assess SFLC in SSc. We show that SFLC are higher in SSc than in controls. Moreover SFLC is significantly correlated with fibrotic involvements of the disease (pulmonary and cutaneous), and with activity and severity. Our results add an additional line of evidence that B cells activation plays probably a role in the pathophysiology of SSc. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4309